A mathematical model for rolling/sliding line contacts in boundary and near boundary lubrication. (November 2015) - Yu, Qingtao; Chang, L; Jeng, Yeau-Ren
This paper presents a mathematical model for rolling/sliding line contacts operating in boundary and near boundary lubrication. The model is developed with first-principle formulations and incorporates key mechanical, thermal and tribo-chemical aspects of the problem including mode of deformation of the contact, friction, flash temperature, boundary film characterization and fluid–solid load sharing. For given load, speeds, bulk temperature and proportion of solid load-sharing, the model outputs a number of variables that are useful for the assessment of the state and severity of the problem. They include contact pressure, temperature, degree of plastic deformation, friction coefficient, friction power intensity, degree of friction-induced junction growth and integrity of the boundary film. The model may be implemented into a gear contact model to study gear systems under loss of lubrication. It may also be integrated with the light mixed-lubrication model of the authors to develop a more complete mixed-lubrication model covering the entire regime of the mixed lubrication. The model is evaluated with a limited scope and more extensive evaluations are needed in time of its validity and applicability through various means and in various settings.